Strategi Guru dalam Membangun karakter Cinta Lingkungan Melalui Pembelajaran IPA di Kelas V SDN Cibuluh 03 Bogor - Ghifari, Isti (Karimah Tauhid, 2024)
The relationship between the environment and humans shows a reciprocal relationship, because humans live in the natural environment and the natural environment needs humans as conservationists. The relationship between humans and the environment should be well maintained until whenever, but currently there are various kinds of damage that occur to the environment. One of the biggest factors causing environmental damage is the lack of awareness and lack of knowledge in humans to protect and preserve the environment. The importance of early education about the understanding of loving and preserving the environment. The goal of this article is analyze the teacher's strategy in improving the character of environmental love through science learning.